Programming ArcGIS with Python cookbook : over 85 hands-on recipes to teach you how to automate your ArcGIS for Desktop geoprocessing tasks using Python - Pimpler, Eric (Quick answers to common problems., 2015)
Programming ArcGIS with Python Cookbook, Second Edition, is written for GIS professionals who wish to revolutionize their ArcGIS workflow with Python. Whether you are new to ArcGIS or a seasoned professional, you almost certainly spend time each day performing various geoprocessing tasks. This book will teach you how to use the Python programming language to automate these geoprocessing tasks and make you a more efficient and effective GIS professional.